Unveiling the effect of molecular weight of vanillic acid grafted chitosan hydrogel films on physical, antioxidant, and antimicrobial properties for application in food packaging - Bakar, Buesra; Pekdemir, Sibel Selcuk; Birhanli, Emre; Ulu, Ahmet; Pekdemir, Mustafa Ersin; Ates, Burhan (Elsevier, 2024)
Till now, a wide range of chitosan (CHS)-based food packaging films have been developed. Yet, the role of molecular weight (MW), which is an important physical property of CHS, in determining the physicochemical and biochemical properties of vanillic acid (VA)-grafted CHS hydrogel films synthesized using CHS with different MWs has not been investigated until now. Three kinds of CHS including low, medium, and high MWs were grafted separately with VA through a carbodiimide mediated coupling reaction. No significant difference in water resistance properties was observed with increasing MW of CHS, in contrast to obvious decrease in light transmittance and opacity. The VA-g-CHS hydrogel films exhibited significantly improved light blocking capacity. A significant improvement in antioxidant (similar to 6-fold) and antimicrobial (similar to 1.2-fold) activity was observed after grafting with VA. In contrast, the free radical scavenging and antimicrobial activity decreased with increasing MW of CHS. Most importantly, VA-g-CHS hydrogel films could maintain the freshness of cherry tomatoes for up to 10 days at similar to 25 degrees C. However, no significant difference was observed depending on the MW value of CHS. This pioneering work is of great importance in guiding the selection of MW of CHS biomacromolecule to design hydrogel films with desired physicochemical and biochemical properties.
Keywords: Chitosan; Vanillic acid; Molecular weight; Hydrogel film; Antioxidant activity; Antimicrobial activity; Food packaging